Knowledge on Japanese people's beliefs in the anime Natsume Yuujinchou - Hamidah, Idah; Kadafi, Muammar; Zuliyanti, Dera (Universitas Dian Nuswantoro, 2018)
Japanese people's trust is a belief inherited from time immemorial and is still maintained today. This can be seen from popular works that still raise traditional Japanese values. One of them is the anime Natsume Yuujinchou raising the values of Japanese people's beliefs about gods or Us and the life of the unseen. This study was about to describe the beliefs of Japanese people found in the anime Natsume Yuujinchou. The research method used to explore Japanese people's trust is a qualitative descriptive method. The approach used is literary anthropology. Found five concepts of Japanese people's beliefs from the anime, namely, 1) trust in the existence of a god; 2) trust in inanimate objects and can live if entered by the spirit; 3) belief in vengeance or punishment invisibly; 4) belief in the manifestations of kindness and evil from the spirit; 5) belief in souls (spirits) or spirits (spirits) in plants or animals The conclusions of this study are Japanese people's beliefs contained in the Natsume Yuujinchou anime in the form of supernatural concepts, soul concepts (souls) and spirits (spirits), and the concept of retaliation (tatari).